Clinical and epidemiological characterization of children with protein-energetic malnutrition - Electra Guerra Domínguez; Yadit Arturo González Carrazana; Frayda Gómez Vázquez; Ana Fandiño Chaveco; Adalgizar Martínez Jiménez (Centro Provincial de Información de Ciencias Médicas, 2018)
A descriptive, longitudinal and prospective study of 76 undernourished children assisted in the Nutrition Service of "Jimmy Hirzel" Polyclinic in Bayamo, Granma province was carried out in the period 2014-2016, with the aim of characterizing them according to variables related to the mothers, the children and the families, for which theoretical, empiric and statistical methods were used. The children with the following characteristics: born underweight (71.1 %), inadequate complementary feeding (61.8 %), repeated acute infections (75.0 %), children which mothers had associated diseases with pregnancy (90.8 %), with low level of knowledge on the disease (67.1 %), as well as coming from families with middle economic incomes (81.6 %) and crowding (55.3 %) prevailed in the case material. It was concluded that most of the undernourished children presented prenatal, natal and postnatal history to kept in mind for the development of malnutrition, which can be preventable or modifiable.